2022-RA-1250-ESGO The MULTISENT study: a multicenter study about the sentinel lymph node biopsy in clinical stage I and II endometrial cancer. (20th October 2022) - Gomez-Hidalgo, Natalia R; Cabrera-Diaz, Silvia; Conesa, Vicente Bebia; Pineda, Virginia Garcia; Iserte, Pablo; Fabregas, Francesc Fargas; Fuste, Pere; Alonso, Paula; Rodriguez, Tomas Gomez; Fernandez, Sergi; Chacon, Enrique; Perez Alvarez, Jose Antonio; et al.
Abstract : Introduction/Background: To evaluate the most accurate technique for sentinel-lymph-node (SLN) biopsy in Endometrial cancer (EC) performed by the different Spanish centers. Methodology: This is a multi-institutional retrospective study including patients with preoperative clinical stage I-II EC FIGO 2009, of all histologies and grades undergoing SLN mapping from January 2015 to January 2022. Patients received three different tracers: Indocyanine green (ICG), ICG + technetium-99m (99mTC) and 99mTC alone and different sites of injections (cervical, uterus and both) were used. Twenty-four Spanish centers were enrolled. Negative SLN were ultra-staged with immunohistochemistry for cytokeratin and OSNA. Results: 1221 patients were analyzed. Median number of resected SLNs was 2 (range 1–3). 526 (43%) patients received ICG, 332 (27.1%) received ICG + 99mTC and 363 (29.7%) 99mTC alone. The cervical injection was used in 1121 (92%) patients, 60 (5%) patients underwent a uterine injection and 40 (3%) patients received both. The bilateral mapping rates were 324 (61.6%) for ICG group, 250 (75.3%) for ICG + 99mTC and 173 (47.7%) for 99mTC alone. The para-aortic mapping rate was 18 (3.4%) for ICG group, 38 (11.5%) for ICG + 99mTC and 25 (6.9%) for 99mTC alone, respectively (p< 0.001). Empty node packets were diagnosed only in 10 (1.6%) patients of the ICG group (p <0.001). The sensitivity was: 77% for ICG group, 90% for ICG + 99mTC and 97% for 99mTC alone. The false negative rate was 23% for the ICG group, 9, 5% for ICG + 99mTC group and 3, 3% 99mTC alone group. Univariate and multivariate analysis showed that age, uterus site of injection and the use of ICG + 99mTC were independent predictive factors of bilateral drainage. Conclusion: We did not find any differences among tracers in terms of accuracy; Otherwise, combining 99mTc to ICG achieves the highest overall and bilateral detection rates.